STEM CELLS: A BRIEF PROGRESSIVE OVERVIEW AND FUTURE PROSPECTS - DHIRENDRA KUMAR SINGH (International Journal of Pharma and Bio Sciences, 2013)
Cell therapy is a new technology that holds great promise for the treatment of many severe diseases. For the past few decades, researchers have been focusing on special cells used for cell therapy known as stem cells. Stem cells have great potential of proliferation and differentiation and high self renewable capacity. Stem cells are the body’s specialized cells from which all other cells with specialized functions are generated. Under the appropriate conditions in the body or in the laboratory, stem cells divide to form more cells called daughter cells which have greater potential either of becoming new stem cells (self-renewal) or specialized cells (differentiation) with a more specific function, such as blood cells, brain cells, heart cells, muscle cells, nerve cells, skin cells, pancreatic cells or bone. Recently successful genetical reprogramming of adult cells have been done to produce induced pluripotent stem cell (iPS) that are very similar to embryonic stem cell.